Tirant Stealthily Invaded Natural Drosophila melanogaster Populations during the Last Century. - Schwarz, F.; Wierzbicki, F.; Senti, K.A.; Kofler, R. (Molecular Biology and Evolution, 2021)
It was long thought that solely three different transposable elements (TEs)-the I-element, the P-element, and hobo-invaded natural Drosophila melanogaster populations within the last century. By sequencing the "living fossils" of Drosophila research, that is, D. melanogaster strains sampled from natural populations at different time points, we show that a fourth TE, Tirant, invaded D. melanogaster populations during the past century. Tirant likely spread in D. melanogaster populations around 1938, followed by the I-element, hobo, and, lastly, the P-element. In addition to the recent insertions of the canonical Tirant, D. melanogaster strains harbor degraded Tirant sequences in the heterochromatin which are likely due to an ancient invasion, likely predating the split of D. melanogaster and D. simulans. These degraded insertions produce distinct piRNAs that were unable to prevent the novel Tirant invasion. In contrast to the I-element, P-element, and hobo, we did not find that Tirant induces any hybrid dysgenesis symptoms. This absence of apparent phenotypic effects may explain the late discovery of the Tirant invasion. Recent Tirant insertions were found in all investigated natural populations. Populations from Tasmania carry distinct Tirant sequences, likely due to a founder effect. By investigating the TE composition of natural populations and strains sampled at different time points, insertion site polymorphisms, piRNAs, and phenotypic effects, we provide a comprehensive study of a natural TE invasion.